Changing Work Goals of Asian Managers: A Comparative Empirical Study in Ten Asian Countries - Chatterjee, Samir Ranjan; Pearson, Cecil (The Haworth Press Inc., 2006)
The seminal research conducted by the Meaning of Working (MOW) International Research Team was undertaken mainly in Western industrialized nations, and that study identified five underlying domains about the meaning of working. One of these domains, the valued work goals, has attracted ongoing attention, and this study aims to add to the literature by reporting managerial perceptions from ten Asian countries. This paper examines the relative importance of a set of 11 work goals, with a sample of 2,466 managers across these ten nations. It may be noted that this research employed the same instrument as the MOW investigation in the early 1980s. Two salient features of the study reported in this paper are firstly, that a number of interesting similarities and differences were observable in relation to the MOW investigation. Secondly, a strikingly convergent of the work goal of “learning” was overwhelmingly seen as the key priority in all nations across all demographic groups. The paper provides an exploratory analysis in an attempt to establish a theoretical underpinning to this empirical evidence.